True Lies - Cameron, James; Art, Malik; Bill Paxton; Jamie Lee Curtis; Tia Carrere; Tom Arnold; Arnold Schwarzenegger (USA 20th Century Fox, 1994)
Harry Tasker is a spy. Presently, he is working on a case involving nuclear warheads in the possession of terrorists. Now his wife doesn't know what he does; as far as she is concerned, he is a computer salesman. Now Harry came close to apprehending the leader of the terrorists but he got away and knows who he is. While Harry tries to pick up his trail, he inadvertently overhead his wife, Helen talking about having a "boyfriend". So, he uses his resources to find out who this guy is. And he learns that he is a car salesman pretending to be what Harry is. When Helen goes to one of their rendezvous, Harry stages an attack on them. He then from behind a shroud, that she could be sent to prison unless she does something for them--plant a bug in a guy's phone. Now she does what she is told but unknown to her the man in the room is Harry, she was about to leave when the terrorists break into the room and take them away. It is there that she finds out who and what Harry is, and it's a good thing cause the terrorists plan to kill when they are through with them.
When a secret agent learns of his wife's extra-marital affair, he pursues her and uses his intelligence resources in a job he kept secret from her.
Language: English
Subtitles: English, Turkish, Spanish
Keywords: Adventure; Comedy; Romance; Thriller; Action